Novel carrier-mediated membrane-assisted three-phase liquid–liquid extraction coupled with liquid chromatography–mass spectrometry for the determination of eight biogenic amines in foods. (1st September 2022) - Zhou, Tian-tian; Yigaimu, Aziguli; Muhammad, Turghun; Jian, Peng-li; Sha, Li-na; Zhang, Shu-biao
Graphical abstract: Highlights: Liquid-liquid extraction (LLE), back extraction and membrane separation integrated via a new U-shaped device. The membrane-assisted three phase LLE (MA-3pLLE) suitable for any LLE system, and for homogeneous and nonhomogeneous samples without prior treatment. High extraction efficiency, reproducibility and less solvent consumption achieved with a proper carrier agent for biogenic amines of broad log P value. Coupling with LC-MS, clean chromatogram and sensitive determination of eight biogenic amines in food achieved without derivatization. Abstract: Analysis of biogenic amines (BAs) is of great importance due to their toxicity and usage as indicators of food freshness. In this study, membrane-assisted three-phase liquid–liquid extraction (MA-3pLLE) was proposed to integrate extraction and back-extraction into a single step using a specially designed U-shaped device. Parameters affecting the performance of the extraction method were optimized. Coupled with liquid chromatography–mass spectrometry, the method was successfully applied for the simultaneous determination of eight BAs without derivatization in apple juice, orange juice, red wine, soy sauce and milk granules, with satisfactory recoveries and RSDs. The calibration curve of the method was linear in the range of 1.00 100.00 ng/mL, with a correlation coefficient ( r 2 ) ≥ 0.9908. The limits of detection were in the range of 0.03 1.00 ng/mL. MA-3pLLE is efficient, reproducible, and green and has great potential for application in the one-step extraction of analytes from complex matrices.